Profile of Amino Acids and Proximate on the Extraction of Red Ginger Protease Enzymes in Commercial Feed for Aquaculture - Yessi Renita Efendi; Eddy Suprayitno; Anik Martinah Hariati (Jurnal Penelitian Pendidikan IPA, 2023)
Quality feed in aquaculture is very important to increase the growth and health of fish. Low feed efficiency can be overcome by feed supplementation using catalytic enzymes. One of the enzymes that can stimulate digestion is protease in red ginger plants. The protease enzyme in red ginger plants plays a role in breaking peptide bonds in place of carboxyl groups so that peptides are formed from complex compounds into simpler compounds. This study aims to determine the profile of amino acids and proximate in feed given red ginger enzymes. This research uses descriptive method. The feed sample used was commercial feed with 4 treatments namely Control (without red ginger enzyme), treatment A (1%), treatment B (3%), and treatment C (5%). The analyzes carried out included red ginger enzyme extraction, protease enzyme purification, proximate and amino acid analysis of each type of feed. The results showed that the results of the SDS-Page analysis on the red ginger protease sample contained at 67.1 kDa. The results of the proximate analysis showed the highest value in feed containing 3% red ginger protease (B) with a percentage of 42.69%. The resulting amino acid content consists of 8 non-essential amino acids namely, L-serine, L-glutamic acid, L-alanine, L-arginine, glycine, L-aspartic acid, L-tyrosine and L-proline. While the essential amino acids consist of 7 types of amino acids namely, L-Phenylalani, L-Isoleucine, L-Valine, L-Lysine, L-Leucine, L-Threonine and L-Histidine. The best type of feed is feed B, which is feed with the addition of 3% red ginger protease.